Localisation of Epithelial Cells Capable of Holoclone Formation In Vitro and Direct Interaction with Stromal Cells in the Native Human Limbal Crypt - Dziasko, Marc A. (Public Library of Science, 2014)
Limbal epithelial stem cells (LESCs) are essential to maintain the transparent ocular surface required for vision. Despite great advances in our understanding of ocular stem cell biology over the last decade, the exact location of the LESC niche remains unclear. In the present study we have used in vitro clonal analysis to confirm that limbal crypts provide a niche for the resident LESCs. We have used high-resolution imaging of the basal epithelial layer at the limbus to identify cells with a morphology consistent with stem cells that were only present within the basal layer of the limbal crypts. These cells are proximal to limbal stromal cells suggesting direct cell-to-cell interaction. Serial block-face scanning electron microscopy (SBFSEM) confirmed that the putative LESCs are indeed in direct contact with cells in the underlying stroma, a contact that is facilitated by focal basement membrane interruptions. Limbal mesenchymal cells previously identified in the human limbus collocate in the crypt-rich limbal stromal area in the vicinity of LESCs and may be involved in the cell-to-cell contact revealed by SBFSEM. We also observed a high population of melanocytes within the basal layer of the limbal crypts. From these observations we present a three dimensional reconstruction of the LESC niche in which the stem cell is closely associated and maintained by both dendritic pigmented limbal melanocytes and elongated limbal stromal cells.